Novel concepts in the epidemiology, diagnosis and prevention of childhood tuberculosis (Swiss Medical Weekly, 2014)
Tuberculosis (TB) is one of the oldest diseases known to mankind, yet it is the second leading cause of death from an infection worldwide today. In the absence of epidemiological data, TB in children was not considered significant and research efforts did not prioritise this group. More recently, there has been renewed interest in childhood TB, leading to improved understanding of the fundamental differences between children and adults in relation to both TB infection and disease. Children with TB infection have a high risk of rapid progression to disease which leads to challenges in diagnosis but also offers the opportunity to investigate biomarkers for infection, progression and protection. This review discusses the most relevant advances in the understanding of epidemiology, diagnosis and prevention of children with TB. It also highlights challenges and research priorities in childhood TB, which include better diagnostic tests, accurate correlates of protection and an improved vaccine.